2017
DOI: 10.1049/iet-epa.2016.0505
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of broken rotor bar fault in open‐ and closed‐loop controlled wye‐connected induction motors using zero‐sequence voltage

Abstract: This study proposes a method to detect and quantify broken rotor bar fault using zero-sequence voltage in a wye-connected squirrel-cage induction motor. The zero-sequence voltage is analysed and two fault severity factors are defined. The factors are almost independent of motor speed and load torque. Furthermore, it is proved that closed-loop control has little influence on the diagnosis results. Consequently, the method can detect broken rotor bar fault for induction motors in both open-and closed-loop drives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19].53] Na A Na A Approximation (7) [19.53-0] Na Na Na Na A: Applicable; Na: Not applicable.…”
Section: Log-energy Entropymentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19].53] Na A Na A Approximation (7) [19.53-0] Na Na Na Na A: Applicable; Na: Not applicable.…”
Section: Log-energy Entropymentioning
confidence: 99%
“…However, these studies were unable to accurately locate fault positions; they could only indicate the phase or zone of faults. When considering a systematic component [25][26][27][28], the voltage and current of all sequences depend on the unbalanced conditions [25]; however, zero-sequence voltage and current can be used to estimate the fault position in a distribution system [26]. Similarly, the Fourier transform (FT) of zero-sequence voltage and current has been employed to obtain the vectors This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: Introductionmentioning
confidence: 99%
“…Various damage types were found, such as interturn short-circuit [1], broken rotor bar [2], bearing inner ring failure, bearing outer ring failure, ball failure, cage failure [3], and eccentricity [4]. As for fault diagnosis of an induction motor, the literature has also indicated that approximately 30% of motor breakdowns are related to stators, 10% to rotors, 40% to bearings, and 20% to other components [5].…”
Section: Introductionmentioning
confidence: 99%